Targeting aurora kinases limits tumour growth through DNA damage‐mediated senescence and blockade of NF‐κB impairs this drug‐induced senescence. Issue 1 (25th November 2012) - Liu, Yan; Hawkins, Oriana E.; Su, Yingjun; Vilgelm, Anna E.; Sobolik, Tammy; Thu, Yee‐Mon; Kantrow, Sara; Splittgerber, Ryan C.; Short, Sarah; Amiri, Katayoun I.; Ecsedy, Jeffery A.; Sosman, Jeffery A.; et al.
Abstract: Oncogene‐induced senescence can provide a protective mechanism against tumour progression. However, production of cytokines and growth factors by senescent cells may contribute to tumour development. Thus, it is unclear whether induction of senescence represents a viable therapeutic approach. Here, using a mouse model with orthotopic implantation of metastatic melanoma tumours taken from 19 patients, we observed that targeting aurora kinases with MLN8054/MLN8237 impaired mitosis, induced senescence and markedly blocked proliferation in patient tumour implants. Importantly, when a subset of tumour‐bearing mice were monitored for tumour progression after pausing MLN8054 treatment, 50% of the tumours did not progress over a 12‐month period. Mechanistic analyses revealed that inhibition of aurora kinases induced polyploidy and the ATM/Chk2 DNA damage response, which mediated senescence and a NF‐κB‐related, senescence‐associated secretory phenotype (SASP). Blockade of IKKβ/NF‐κB led to reversal of MLN8237‐induced senescence and SASP. Results demonstrate that removal of senescent tumour cells by infiltrating myeloid cells is crucial for inhibition of tumour re‐growth. Altogether, these data demonstrate that induction of senescence, coupled with immune surveillance, can limit melanoma growth. Abstract : The authors suggest that aurora kinase inhibitors may effectively slow tumour growth via senescence to provide effective therapy for certain melanoma patients.